Developmental surveillance in primary health care: absence of child development milestones and associated factors - Katherine Solís-Cordero; Claudia Nery Teixeira Palombo; Luciane Simões Duarte; Rebeca Ishi Munhoz; Aurea Tamami Minagawa Toriyama; Ana Luiza Vilela Borges; Elizabeth Fujimori (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to identify the absence of one or more general child development milestones and by domains, and associated factors. Methods: cross-sectional study with 334 children under three years of age conducted out at Primary Health Care Facilities, São Paulo, Brazil. The dependent variable was the general child development and the fine motor, gross motor, social and psychic domains evaluated using the Developmental Surveillance Instrument of the Brazilian Ministry of Health. Data were obtained by interviewing the mothers and observing children. The chi-square test and logistic regression analyses were used. Results: absence of one or more milestones of general child development was found in 52.1% of children, especially, in the fine motor domain. We found an association between general child development with age (OR = 4.4; CI95%= 2.0-9.9) and the place of stay of the child who does not attend daycare (OR = 3.7; CI95%= 1.3-10.5). Conclusions: the absence of one or more milestones of general child development is high and associated with aspects of the child and the environment. This emphasizes the importance of promoting developmental surveillance in Primary Health Care Facilities among health professionals using the official instrument recommended by the Brazilian Ministry of Health.